Individual- and Population-Level Impacts of Traumatic Brain Injury and Maternal Characteristics on Subsequent Offending Behavior - Wand, H.; Simpson, M.; Malacova, Eva; Schofield, P.; Preen, D.; Tate, R.; Butler, Tony (Lippincott Williams & Wilkins, 2017)
Copyright © 2017 Wolters Kluwer Health, Inc. All rights reserved. OBJECTIVE:: To evaluate the individual- and population-level impact of a combination of factors, including traumatic brain injury (TBI) and certain maternal characteristics, on subsequent criminal conviction. DESIGN AND PARTICIPANTS:: A retrospective record linkage study involving a cohort of 30 599 individuals born between 1980 and 1985, with ratio of 1 (with TBI): 3 (no TBI), matched by sex and the year of birth. METHODS AND PROCEDURES:: Cox proportional hazard regression models and population attributable risk percentages (PAR%) were used to assess the contribution of TBI and other risk factors on subsequent criminal convictions. MAIN OUTCOMES AND RESULTS:: Overall, individuals born to the teenaged mothers ( < 20 years) have significantly higher proportion of TBI than those born to older mothers (35% vs 22%; P < .001). In the gender-specific analyses, a history of TBI was associated with increased risk for criminal convictions (adjusted hazard ratio [aHR]: 1.48, 95% confidence interval [CI] : 1.36-1.60, and aHR: 1.45, 95% CI: 1.22-1.73, for men and women, respectively). Maternal characteristics (maternal age, single parent, multiparity) were identified as the greater contributor to the criminal convictions (PAR%: 57% and 67% for men and women, respectively). The combined impact of mental illness, maternal factors, and TBI was estimated to be 67% and 74% (for men and women, respectively); with nonoverlapping 95% CIs for PAR%, these factors were estimated to have had a higher impact among females than among males. CONCLUSION:: More than half of the criminal convictions were associated with a relatively small number of risk factors, including poor mental health, low socioeconomic status, and TBI as well as certain maternal characteristics.